Kesejahteraan Psikologis Sebagai Tujuan Aksiologis Bimbingan dan Konseling: Tinjauan Filsafat Ilmu - Kartini Haryani; Akhmad Fajar Prasetya (Lembaga Pengembangan Kinerja Dosen, 2026)
Psychological well-being is a fundamental construct in individual development; however, within guidance and counseling practice it is often positioned merely as an indirect outcome of problem-focused interventions. Philosophically and empirically, psychological well-being holds substantial potential to be established as a primary goal of guidance and counseling services. This article aims to examine psychological well-being as an axiological objective of guidance and counseling through a philosophy of science perspective supported by recent empirical evidence. The method employed is a literature review of scholarly publications from the last eight years retrieved through Google Scholar. Eleven relevant articles were selected and analyzed using thematic synthesis to identify conceptual patterns and empirical findings related to psychological well-being in the context of guidance and counseling. The results indicate that psychological well-being is conceptualized as a long-term developmental outcome reflecting holistic human functioning, encompassing dimensions such as autonomy, purpose in life, personal growth, environmental mastery, self-acceptance, and positive relations with others. Various guidance and counseling interventions particularly those based on mindfulness and positive psychology interventions have been empirically demonstrated to effectively enhance eudaimonic well-being. From an axiological perspective, psychological well-being possesses strong value foundations and aligns with the ethical mandate of guidance and counseling to promote optimal human development. This article underscores the necessity of a paradigm shift in guidance and counseling practice, moving from a predominantly problem-oriented approach toward a well-being-oriented framework in which psychological well-being is positioned as a central and explicit goal of professional services.